1997
DOI: 10.1590/s0103-90161997000100008
|View full text |Cite
|
Sign up to set email alerts
|

SINTOMAS DE DESORDENS NUTRICIONAIS EM ESTÉVIA Stevia rebaudiana (Bert.) Bertoni

Abstract: São descritos e discutidos os sintomas de deficiência de N, P, K, Ca, Mg e B, e de toxicidade de B e Zn, em estévia cultivada em solução nutritiva. -N: desenvolvimento reduzido, folhas pequenas, pouca ramificação, e amarelecimento generalizado. -P: crescimento reduzido. -K: folhas encurvadas, precocemente, para baixo, aparentando menor teor de água; amarelecimento e necrose das folhas mais velhas e menor proporção de ramos. -Ca: pontuações escuras, clorose e necrose nas folhas, além de murchamento e colapso da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Similarly, application of N-, P-, or K-based fertilizers did not change steviol glycoside levels, but did cause precocious flower budding. ,− Visual symptoms of nutrient deficiency in S. rebaudiana include changes in leaf color to dark green (P, B), yellow (N, K), or pale green (chlorosis; S, Mg), sometimes mottled (K) or with dark necrotic spots (Ca, K, S), and an impairment of overall growth (N, P). These deficiencies reduced steviol glycoside levels within the leaves, with the most severe decreases generally observed in Ca, K, and S deficiencies. , On the other hand, addition of 5 ppm B to hydroponically grown plants resulted in 50% higher yields of stevioside ( 37 ) and rebaudioside A ( 38 ). , Addition of Zn may also increase steviol glycoside levels significantly . Studies with in vitro cultures further showed that the addition of 3–5% sucrose could effectively increase steviol glycoside production. , …”
Section: Accumulation Of Steviol Glycosides In Stevia Rebaudianamentioning
confidence: 99%
“…Similarly, application of N-, P-, or K-based fertilizers did not change steviol glycoside levels, but did cause precocious flower budding. ,− Visual symptoms of nutrient deficiency in S. rebaudiana include changes in leaf color to dark green (P, B), yellow (N, K), or pale green (chlorosis; S, Mg), sometimes mottled (K) or with dark necrotic spots (Ca, K, S), and an impairment of overall growth (N, P). These deficiencies reduced steviol glycoside levels within the leaves, with the most severe decreases generally observed in Ca, K, and S deficiencies. , On the other hand, addition of 5 ppm B to hydroponically grown plants resulted in 50% higher yields of stevioside ( 37 ) and rebaudioside A ( 38 ). , Addition of Zn may also increase steviol glycoside levels significantly . Studies with in vitro cultures further showed that the addition of 3–5% sucrose could effectively increase steviol glycoside production. , …”
Section: Accumulation Of Steviol Glycosides In Stevia Rebaudianamentioning
confidence: 99%
“…Boron deficiency, in general, reduces root growth (Lima Filho and Malavolta, 1997;Viegas et al, 2004) and in the coconut palm tree, production of total roots is reduced by 30% and of thin roots by 48% ( Pinho et al 2008a), Sobral (1998), Broschat (2005, and Santos et al (2003) observed that boron deficiency also damages the plant aerial part ,which produces less expanded young leaves with signs of blighted, necrotic, and corky areas. The primary symptoms of B deficiency in coconut trees are leaflet tip truncation, leaf crumpling or distortion, and failure of the spear leaf to open normally.…”
Section: Introductionmentioning
confidence: 99%
“…Fernandes et al (2013), studying nutritional deficiencies of macronutrients and sodium in peach palm seedlings, observed that seedlings deficient in P showed an increase in the length of the primary roots and a smaller amount of root hairs. B deficiency, in turn, can reduce the production of total and thin roots, cause thickening of the roots and short branches (Lima Filho and Malavolta, 1997;Salvador et al, 1999;Pinho et al, 2008). Well-developed roots represent an increase in the dry matter production capacity of plants, as they are responsible for the water and nutrients uptake, besides the storage of carbohydrates and proteins responsible for the production and continuity of the plant.…”
Section: Resultsmentioning
confidence: 99%